KADAR PROTEIN, VITAMIN C, DAN SIFAT ORGANOLEPTIK BUBUR BAYI DARI CAMPURAN TEPUNG KECAMBAH KACANG-KACANGAN DAN JAGUNG - Mohammad Junaidi; Joko Teguh Isworo (Universitas Muhammadiyah Semarang, 2011)
Legumens is a protein recources with corns are completing each other. The goal of this research is to know the profile of protein, vitamin C, and organoleptic characteristic of baby’s porridge from mixture of legumens sprout and corn flour. Variation of the mixture of sprout from legumens (soybean, brown bean and mung bean (50%,75%) and sprout of corn (25%,50%). The result of the research shows that there is an influence from variety of the mixture of legumens sprout and corn flour toward contents of protein, vitamin C, and organoleptic characteristic (color, taste, and texture). The highest protein contents in the mixture of sprout of brown bean 75% and corn 25% (18,389 g %) and vitamin C in the mixture of sprout of brown bean 50% and corn 50%, (20 mg %) and organoleptic characteristic in the mixture of sprout of brown bean 75% and corn 25% with the score 4,75.